Clause typing in the Old Irish verbal complex morphological expression, paradigmatic organization, and syntactic implications - García Castillero, Carlos (Trends in linguistics. Studies and monographs ;, 2020)
This monograph offers a systematic description of the expression of clause typing in the Old Irish (7th-9th AD) verbal complex and discusses some of its diachronic aspects. The available evidence is rich enough as to make relevant statements about the morphosyntactic and pragmatic aspects of this specific topic, which had not been considered systematically in previous descriptive or diachronic studies on the Old Irish verbal morphosyntax.